Analisis Kelimpahan dan Jenis Mikroplastik pada Sedimen di Pesisir Desa Pemuteran, Bali - Silalahi, Sarah Kristiani; Hendrawan, I Gede; Yogi Darmendra, I Putu (Journal of Marine Research and Technology; Vol 8 No 1 (2025): FEBRUARI 2025DO - 10.24843/JMRT.2025.v08.i01.p02, 2025)
Plastic waste that enters the water will be degraded into micro particles (<5 mm) known as microplastics.   Anthropogenic activities in coastal areas are suspected to be one of the contributing factors to marine debris input. The aim of this research is to determine the abundance and types of microplastics in sediment on the coast of Pemuteran Village, Bali. The sediment sampling method used a purposive sampling method at 4 stations with different environments and taken in the intertidal zone area. Then ex situ processing was carried out by drying, density separation, Wet Peroxide Oxidation (WPO), and filtering, and identified using a stereo microscope. The abundance of samples was calculated based on type, color, size and total abundance and analyzed using one-way ANOVA test statistics. The research results showed that there were 3 types of microplastics found, namely fiber (147 particles), film (18 particles), and fragments (6 particles). The type of microplastic that dominates each station is the fiber type. Several colors of microplastics were found, namely orange, white, red, purple, brown, transparent, green and blue which were the most dominant colors. The dominant size of microplastics is in the range of 0.5-1 mm with 48 particles. The highest total average abundance of microplastics was found at station 2, namely, 35.56 ± 10.44 particles/kg. The total abundance of microplastics at each station did not show significant differences, but there were significant differences in abundance based on type, color and size.